2009
DOI: 10.1210/en.2008-1432
|View full text |Cite
|
Sign up to set email alerts
|

The Orexigenic Activity of the Hypothalamic Neuropeptide 26RFa Is Mediated by the Neuropeptide Y and Proopiomelanocortin Neurons of the Arcuate Nucleus

Abstract: 26RFa is a hypothalamic RFamide neuropeptide that was identified as the endogenous ligand of the orphan G protein-coupled receptor, GPR103, and that stimulates appetite in mice. Up until now, the mechanism of action of 26RFa in the hypothalamic control of food intake remains unknown. The high density of GPR103 in the arcuate nucleus (Arc) prompted us to investigate, in the present study, the effects of 26RFa on the rat neuropeptide Y (NPY)/proopiomelanocortin (POMC) system. Intracerebroventricular injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 42 publications
4
73
1
4
Order By: Relevance
“…This sequence similarity and lack of identity suggests that QRFP receptors diverged from orexin receptors earlier than NPFF receptors but experienced selective pressure to retain homologous sequence. Reported responses to central administration of QRF peptides, the ligands for QRFP receptor, include increases in arousal and locomotor activity, increased feeding, energy balance regulation, and the modulation of pain responses (Thuau et al, 2005;Moriya et al, 2006;Takayasu et al, 2006;Yamamoto et al, 2008;Lectez et al, 2009;Yamamoto et al, 2009), functions remarkably similar to that of orexin.…”
Section: Orexin Receptor Structure Ismentioning
confidence: 99%
“…This sequence similarity and lack of identity suggests that QRFP receptors diverged from orexin receptors earlier than NPFF receptors but experienced selective pressure to retain homologous sequence. Reported responses to central administration of QRF peptides, the ligands for QRFP receptor, include increases in arousal and locomotor activity, increased feeding, energy balance regulation, and the modulation of pain responses (Thuau et al, 2005;Moriya et al, 2006;Takayasu et al, 2006;Yamamoto et al, 2008;Lectez et al, 2009;Yamamoto et al, 2009), functions remarkably similar to that of orexin.…”
Section: Orexin Receptor Structure Ismentioning
confidence: 99%
“…Neuroanatomical observations revealed that 26RFa-and GPR103-expressing neurons are primarily localized in hypothalamic nuclei involved in the control of feeding behavior (1,2,5,7). Indeed, intracerebroventricular administration of 26RFa or 43RFa stimulates food intake (1,5,8,9), and the neuropeptide exerts its orexigenic activity by modulating the neuropeptide Y/proopiomelanocortin system in the arcuate nucleus (9). Chronic injection of 43RFa induces a significant increase in mice body weight and fat mass, which is associated with a hyperphagic behavior (8), and the orexigenic activities of 26RFa and 43RFa are more robust in rodents fed a high-fat diet (8,10).…”
mentioning
confidence: 99%
“…In humans and rodents, 43RFa, 26RFa, and GPR103 are mainly expressed in brain, particularly in the hypothalamus (8), as well as in peripheral tissues, including the eye, testis, thyroid, adipose tissue, and macrophages (6,(9)(10)(11). 43RFa and 26RFa have been implicated in many physiological functions, including stimulation of food intake (5,(12)(13)(14)(15)(16)(17), regulation of gonadotropic axis (18,19), aldosterone secretion (7,20), bone formation (21), adipogenesis and inflammation (10,11), blood pressure (12), and prostate cancer differentiation and migration (22).…”
mentioning
confidence: 99%